SPIKING SCHOOL ACHIEVEMENT ON NATIONAL STANDARDS THROUGH TEACHER MANAGEMENT INFORMATION SYSTEM AT MUHAMMADIYAH 5 ELEMENTARY SCHOOL - Ega JANUARDI; Connie CHAIRUNNISA (Journal of Education and Leadership in Education, 2019)
This research was conducted to determine the success of the Teacher Management Information System in raising the achievement of the national standard at Muhammadiyah 5 Elementary School-5, Jakarta. It focuses on data collection systems of teachers through Google Drive (GDrive). The researcher used a Goal-Oriented Evaluation Model. The result showed that the program could help school increase the achievement of three out of eight national standards of education, namely the standard of facilities and infrastructure, the standard of management, and the standard of educator and non-educator. The research recommends the program to be continued with improvement. To get maximum results, the principal has to conduct a structured training program followed by establishing a good teacher filing system.